Fabrication Of Anisotropic Poly (4-Methyl-1-Pentene) Membrane For CO2 And N2 Gas Separation - Zainuddin, Muhd Izzudin Fikry (Universiti Sains Malaysia, 2021)
Carbon dioxide (CO2) separation from flue gas with the use of membrane technology has become the focus of researchers over the past decades due to its lower energy consumption and cheaper alternative. In this thesis, anisotropic poly (4-methyl-1-pentene) (PMP) was studied to determine the feasibility of using PMP to separate CO2 from nitrogen (N2) gas. A full dense PMP membrane with various PMP wt% was fabricated at both 20 and 70 ℃ to determine the effect of temperature on dense layer of the membrane. Water contact angle and FTIR-ATR was used to characterize the fabricated PMP membrane. The water contact angle of PMP membrane surface without modification such as plasma treatment or coating that have been obtained ranged between 105⁰ and 116⁰ which makes the membrane to be classified as hydrophobic membrane. The SEM image on the cross section of the full dense PMP membrane also showed no significant difference of the dense layer between the membrane that undergo dry phase inversion at 20 ℃ and 70 ℃. CO2 and N2 gas permeance as well as the selectivity does not differ greatly with fabrication temperature. 5 wt% PMP fabricated at 20 ℃ seems to be the best condition to fabricate anisotropic PMP membrane based on the gas permeance test. The CO2 and N2 permeance is 5.91 ± 0.29 GPU and 0.51 ± 0.03 GPU respectively, and with CO2/N2 selectivity as 11.57 ± 0.10. The parameter was then used to fabricate anisotropic PMP membrane with varying dry phase inversion time from 10 to 60 seconds. The CO2 permeance increased by 10 times while the N2 permeance increased by 5 times on average which makes the CO2/N2 selectivity dropped by half from the full dense PMP membrane. SEM imaging is used to observe the effect of dry phase inversion time on the thickness of the dense layer of the fabricated anisotropic PMP membrane. With 40 second dry phase inversion time, it appears to be the best duration to fabricate the anisotropic PMP membrane. The CO2 and N2 permeance is recorded to be 51.49 ± 1.56 GPU and 9.90 ± 0.58 GPU respectively with selectivity of CO2/N2 gas as 5.21 ± 0.15 with the least deviation. Water-ethanol mixture is not suitable as coagulation bath due to the immiscibility between cyclohexane and water. Using higher alcohol chain will reduce the solubility parameter between cyclohexane and the alcohol which will cause the reduction in porosity of the PMP membrane in the porous section. In our case, we conclude that introducing water component as a mixture to the coagulation bath is not suitable for the production of PMP membrane with cyclohexane as its solvent as water and cyclohexane is immiscible and will form two-phase system.